2019
DOI: 10.1002/chem.201900715
|View full text |Cite
|
Sign up to set email alerts
|

All Non‐Carbon B3NO2 Exotic Heterocycles: Synthesis, Dynamics, and Catalysis

Abstract: The B3NO2 six‐membered heterocycle (1,3‐dioxa‐5‐aza‐2,4,6‐triborinane=DATB), comprising three different non‐carbon period 2 elements, has been recently demonstrated to be a powerful catalyst for dehydrative condensation of carboxylic acids and amines. The tedious synthesis of DATB, however, has significantly diminished its utility as a catalyst, and thus the inherent chemical properties of the ring system have remained virtually unexplored. Here, a general and facile synthetic strategy that harnesses a pyrimid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…[61] As the synthesis of the first generation catalysts was tedious, a more facile approach to equally potent DATBs analogs based on pyrimidines (Pym-DATBs) was reported in 2019. [62] DATBs were also applied to the coupling of standard Fmoc protected amino acids amino acids to yield simple polypeptides [63] that included sidechains featuring…”
Section: Diboron Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] As the synthesis of the first generation catalysts was tedious, a more facile approach to equally potent DATBs analogs based on pyrimidines (Pym-DATBs) was reported in 2019. [62] DATBs were also applied to the coupling of standard Fmoc protected amino acids amino acids to yield simple polypeptides [63] that included sidechains featuring…”
Section: Diboron Catalystsmentioning
confidence: 99%
“…Yamamoto. [120] Furthermore, if a stereoselective variant of this sys- Kumagi [62,63] Yamamoto (methyl ester amidation [121] )…”
Section: Nhcs and Organocatalystsmentioning
confidence: 99%
“…Intriguing protocols for amidation without the necessity of reagents have been recently established based on boron,47 hafnium and zirconium8 Lewis acid catalysts, for example 1e,g–k,m. The latest generation of catalysts such as the remarkable dioxoazatriborinane of Shibasaki and Kumagai, which is prepared in five steps, allows even for the synthesis of amides derived from challenging aromatic and sterically encumbered aliphatic carboxylic acids 6,7…”
Section: Introductionmentioning
confidence: 99%
“…[12] A number of newer boronic acids and borate catalysts were described that efficiently promote the direct amide bond formation of aliphatic amines at temperatures ranging from ambient to moderate, and over 100 °C. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For example, 5-methoxy-2-iodophenyl boronic acid (MIBA), [15][16][17] a catalyst developed in this laboratory, affords amide products of aliphatic amines and carboxylic acids in high yields within reaction times of 2-48 hours at ambient temperature. In a significant advance, Ishihara and co-workers reported that 3,5bis(trifluoromethyl)phenylboronic acid, when used in cooperation with 4-(N,N-dimethylamino)pyridine N-oxide (DMAPO), can catalyze the direct amidation reaction of hindered aliphatic and less reactive aromatic carboxylic acids under azeotropic reflux conditions.…”
Section: Introductionmentioning
confidence: 99%